PROFITABILITAS DAN CORPORATE GOVERNANCE PADA TAX AVOIDANCE - Rizka Rachmah Putri; Diana Gustinya (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research was conducted to determine the partial effect of Profitability and Corporate Governance on Tax Avoidance in Manufacturing Companies in the Basic Industry and Chemical Sector Registered on the Bei for the 2019-2021 Period. This research was conducted at manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The data analysis technique used is a quantitative research method with a descriptive approach. The type of data used is secondary data obtained from the Indonesia Stock Exchange (IDX). The method of determining the sample of this study using purposive sampling. The total population in this study were 75 companies. There are 18 companies that meet the criteria to be sampled in this study. This study was tested by multiple linear regression analysis using the SPSS version 25 program. Based on the partial results of the study, it shows that Profitability and Managerial Ownership have a significant effect on Tax Avoidance. Meanwhile, the audit committee, independent board of commissioners and institutional ownership have no significant effect on tax avoidance.